Análisis de la Identidad Laboral y el sin Sentido en Relación al Trabajo Tercerizado - Sánchez-Flores, Bruno; Kurezyn-Díaz, Crishelen; González-Pérez, Manuel (European Scientific Journal, ESJ, 2017)
Labor identity (LI) is a fundamental aspect of the worker. Without it, we are prone to generate nonsense for our work. Labor Outsourcing (LO) is a form of work that encourages the loss of LI and it has as a consequence on the nonsense of work (NW). The aim of this research is to investigate the correlation between LI and loss of consciousness in the LO context. To address this research, a quantitative research was conducted. A total sample of 55 people, composed of men and women between 25 and 56 years old, was used. Respondents were working on the outsourcing scheme in the personnel supply modality. The instrument that was applied was based on individual elaboration. Findings on the basis of NW and LI show high positive rates. Based on this, we can say that, despite the fact that workers live this precarious modality of work, they are motivated. However, we found that this absence of NW and presumed LI as a function of LO, is actually an apparent factor. This is due to the key items I2, SS3, T1 and T5 that has helped us to find the necessary support to affirm the existence of an aspirational LI feeling that generates the meaning of the work. Finally, we conclude that LO is perceived by the sample as a possible means to be directly employed by the primary organization of work.